Influence of surface sealants on microleakage of composite resin restorations - Santos, Paulo Henrique dos [UNESP]; Assunção, Wirley Goncalves [UNESP]; Pavan, Sabrina [UNESP]; Consani, Simonides; Correr-Sobrinho, Lourenço; Sinhoreti, Mario Alexandre Coelho [UNESP] (My University, 2008)
Purpose: The purpose of this study was to verify the influence of surface sealants and dentin adhesive systems on the microleakage of composite restorations. Methods: Class V cavities were made on the buccal faces of 100 permanent third molars and restored with Z250. After 24 hours, they were submitted to polishing and finishing processes. The teeth were divided into groups according to the sealant agent: group 1 - Single Bond; group 2 - Opti Bond Solo Plus; group 3 - Fortify; group 4 - Fortify Plus; and group 5 - control without sealant. The analysis of immediate microleakage was performed in 10 restorations from each group, soon after the sealing. The other 10 specimens from each group were submitted to tooth-brushing and thermal cycles. The teeth were isolated and immersed in 2% methylene blue solution, washed in tap water, and sectioned in the buccolingual direction. The percentage of marginal leakage was calculated using an image analysis program, and results were submitted to analysis of variance and Tukey's test. Results: All the sealed groups demonstrated lower microleakage values compared to the control group. Group 3, sealed with Fortify, presented the lowest mean microleakage values. Conclusion: The application of surface sealants effectively decreased the microleakage in composite resin restorations.
Keywords: Coating; Composite hard tissue; In vitro; bisphenol A bis(2 hydroxypropyl) ether dimethacrylate; dentin bonding agent; Fortify sealant; OptiBond SOLO; resin; resin cement; single bond; dental care; dental surgery; endodontics; human; methodology; molar tooth; tooth disease; Bisphenol A-Glycidyl Methacrylate; Composite Resins; Dental Leakage; Dental Restoration, Permanent; Dental Stress Analysis; Dentin-Bonding Agents; Humans; Marginal Adaptation (Dentistry); Molar, Third; Resin Cements